(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The growing concern among wildlife experts and the public regarding animal health and illnesses is a major trend in wildlife management. Simultaneously, the wildlife profession is reconsidering the ramifications of managing wild populations as a people’s confidence, as well as the obligation that comes with it to preserve the quality (i.e., health) and long-term viability of wildlife. It’s an excellent time to emphasise the importance of wildlife health as well as to advocate for comprehensive and consistent wildlife health integration in wildlife management. Researchers look at how public trust principles have been applied to animal population control in the United States in this research. Humans feel that wildlife health is vital to fulfilling public trust administration obligations with relation to wildlife since it is trustees’ principal responsibility to protect the well-being of wildlife species (i.e., the core resources of the trust). Since both wildlife hazard - health perception about the threats posed by wildlife diseases to humans and household pets are rising issues, wildlife sickness and risk communication in connection to wildlife health are vital to wildlife trust management. We suggest that wildlife health specialists are critical to maintaining the wildlife trust, and that current conditions enable wildlife health care professionals to contribute significantly to wildlife management.